Alexander von Humboldt’s Footnotes: “Networks of Knowledge” in the Sources of the 1826 Essai politique sur l’île de Cuba - Werner, Anja (HiN - Alexander von Humboldt in the Net. International Review for Humboldt Studies, 2014)
AbstractWhen it comes to footnotes, Alexander von Humboldt was ahead of his times even though his references leave much to be desired by today’s academic standards. This article examines the footnotes of Humboldt’s Essai politique sur l’île de Cuba (1826). While it is not always easy to decipher his sometimes cryptic references, the undertaking is worthwhile: Humboldt’s footnotes do not only reveal his vast networks of knowledge. They also provide glimpses of ongoing, contemporary disputes among different scholars that involve Humboldt’s writings. They also present Humboldt’s reactions to such disputes. Exploring Humboldt’s footnotes consequently allows the reader to access both Humboldt the scholar and Humboldt the human being. ZusammenfassungAlexander von Humboldts Fußnoten waren ihrer Zeit weit voraus, obwohl sie kaum den heutigen akademischen Standards entsprechen. Dieser Artikel untersucht die Fußnoten in Humboldts Essai politique sur l’île de Cuba (1826). Zwar ist es nicht immer leicht, die manchmal recht geheimnisvollen Verweise zu entschlüsseln, dennoch lohnt sich der Versuch: Humboldts Fußnoten geben nicht nur Auskunft über seine umfassenden Netzwerke des Wissens. Sie verweisen auch auf Auseinandersetzungen verschiedener Gelehrter über Humboldts Schriften. Schließlich beinhalten sie Humboldts Reaktionen auf solche Auseinandersetzungen. Eine Untersuchung von Humboldts Fußnoten erlaubt es folglich dem Leser, mehr über Humboldt den Wissenschaftler aber auch Humboldt den Mensch zu erfahren. RésuméQuand il s’agit de notes, Alexandre de Humboldt était en avance sur son temps, même si ses références laissent beaucoup à désirer par rapport aux normes universitaires d’aujourd’hui. Cet article examine les notes de l’Essai politique sur l’île de Cuba (1826). Même s’il n’est pas toujours facile de déchiffrer ses références parfois cryptiques, l’entreprise vaut la peine: les notes de Humboldt ne révèlent pas seulement ses vastes réseaux de savoir. Ils fournissent également des aperçus de conflits contemporains en cours entre les différents spécialistes qui s’occupent des écrits de Humboldt. Ils présentent également les réactions de Humboldt à de tels différends. Explorer les notes de Humboldt permet donc au lecteur d’accéder à la fois Humboldt le savant et Humboldt l’être humain.